Recycled polyester resin and method for producing same
Patent Information
- Application Number
- JP2020163692
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-29
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2040-09-29
AI Technical Summary
【0016】 本発明の再生ポリエステル樹脂は、a)使用済みポリエステル製品及びb)ポリエステル製品を製造する工程で発生する未採用ポリエステルの少なくとも1種のリサイクルポリエステル原料を含有しながらも、異物の混入量が少なく、かつカルボキシル末端基濃度、ジエチレングリコールの含有量が特定の範囲を満足し、熱安定性に優れるものである。このため、例えば溶融紡糸により繊維を得る工程、成膜によりシートまたはフィルムを得る工程、ボトル等の成形品を得る工程において、比較的長期にわたる連続運転が可能となり、生産性良く各種の形態の製品を製造することができる。そして、再生ポリエステル樹脂でありながら共重合成分を含む共重合ポリエステル樹脂であるため、透明性が求められるボトル等の成形品や接着性が求められる繊維用途にも好適に使用することができる。 また、本発明の再生ポリエステル樹脂の製造方法によれば、複雑な工程や装置を必要とせず、操業性よく低コストで本発明の再生ポリエステル樹脂を得ることが可能であり、実用上のメリットが大きいものである。
Smart Images

Figure 0007644440000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel recycled polyester resin and a method for producing the same. In particular, the present invention relates to a recycled polyester resin produced from recycled polyester raw materials derived from used polyester products as well as recycled polyester raw materials derived from unused polyester generated in the process of producing polyester products, which has a low amount of foreign matter mixed in and can be processed into various molded products in the same way as virgin polyester resin, and a method for producing the same. [Background technology]
[0002] Polyethylene terephthalate (hereinafter sometimes abbreviated as PET) has a high melting point, is resistant to chemicals, and is relatively low cost, so it is widely used in fibers, films, and molded products such as PET bottles. These polyester products inevitably generate waste during the manufacturing and processing stages, and are often disposed of after use, but if they are incinerated, the high heat generated will cause significant damage to the incinerator and shorten its lifespan, while if they are not incinerated, they will remain semi-permanently as they do not decompose. In recent years, it has become a problem that once-used polyester products, such as plastic containers discarded as garbage, end up in rivers and into the ocean, where microplastics are broken down into small pieces by the action of waves and tides, accumulate in the bodies of marine organisms, and are concentrated up the food chain, adversely affecting the marine ecosystem. Plastic is a major cause of marine pollution, and there is a global movement to reduce the use of plastics and switch to biodegradable plastics.
[0003] From the viewpoint of reducing the amount of plastic products used and from the viewpoint of environmental issues, various methods of recycling are being used to reuse resources. Regarding polyester products, methods of recycling polyester waste generated during the manufacturing process and methods of recovering products that were once on the market and discarded and reusing them as raw materials are being considered. In particular, in recent years, products that have been given the Eco Mark, which is certified as having achieved a certain recycling rate, have become widespread for textile products.
[0004] Various methods have been proposed for recycling recycled polyester raw materials, such as a method of adding methanol to PET scraps to decompose them into dimethylene terephthalate (hereinafter sometimes referred to as "DMT") and ethylene glycol (hereinafter sometimes referred to as "EG") (Patent Document 1), a method of adding EG to PET scraps to depolymerize them, and then adding methanol to recover DMT (Patent Document 2), and a method of depolymerizing PET scraps with EG to form oligomers, which are then used in a polycondensation reaction (Patent Document 3).
[0005] In addition, problems that arise when recycling PET bottles that have already been made into products include additives added to the polyester resin and items attached to the bottle itself, such as caps (aluminum, polypropylene, polyethylene), inner stoppers and liners (polypropylene, polyethylene), labels (paper, resins such as polystyrene, ink), adhesives, printing ink, etc. As a pre-treatment for the recycling process, the collected PET bottles are first put through a vibrating sieve to remove sand, metal, etc. The PET bottles are then washed, and the colored bottles are separated before being roughly crushed. Labels and other items are then removed by wind separation. Aluminum pieces from the caps and other parts are then removed and the PET bottle pieces are finely crushed. Components such as adhesives, proteins, and mold are removed by high-temperature alkaline washing, and heterogeneous components such as polypropylene and polyethylene are separated by specific gravity.
[0006] However, even after these steps, it was difficult to separate non-polyester resins such as polypropylene, polyethylene, and polystyrene from PET resin. Therefore, even if recycled polyester resins were obtained by the recycling methods described in Patent Documents 1 to 3, foreign matter derived from non-polyester resins could not be sufficiently removed, and the amount of foreign matter mixed in could not be sufficiently reduced, so it was not possible to obtain a product having the same quality as virgin polyester resin. Moreover, the methods described in Patent Documents 1 to 3 require a large amount of cost for the installation, operation, maintenance, etc. of the recovery equipment, and there is room for improvement in terms of practicality.
[0007] In addition, the invention described in Patent Document 4 describes a method in which polyester waste is depolymerized with ethylene glycol, filtered through a filter with an average mesh size of 10 to 50 μm, and then repolymerized. It is also shown that the obtained recycled polyester resin has a small amount of foreign matter mixed in and is excellent in operability during processing. However, even with this method, the foreign matter derived from the non-polyester resin as described above cannot be sufficiently removed, and the amount of foreign matter mixed in cannot be sufficiently reduced.
[0008] In general, in the manufacture of plastic bottles and the like, the so-called blow molding method is adopted, in which a molten plasticized resin is extruded through a die orifice to form a cylindrical parison, which is then sandwiched between dies and air is blown into it, because of the ease of molding, high productivity, and relatively low equipment costs for molding machines, dies, etc. From the viewpoint of environmental issues, the use of recycled polyester resins in such blow molded products is also being considered.
[0009] Furthermore, since crystallization is likely to occur during blow molding, even if molding is possible, there is a problem in that whitening occurs and transparency becomes insufficient. In order to improve transparency, polyester resins in which polyethylene terephthalate is copolymerized with other monomer components have been proposed (see, for example, Patent Document 5).
[0010] Generally, hot melt binder fibers are widely used for the purpose of bonding fibers constituting stuffing for pillows and bedding, quilting stuffing, mattress stuffing, etc. Among them, copolymer polyester resins mainly composed of terephthalic acid, isophthalic acid, and ethylene glycol are widely used as polyester binder fibers.
[0011] Thus, there is a great demand for copolymer polyester resins using recycled polyester raw materials in various molded articles and fiber products, but a copolymer polyester resin that can be sufficiently removed not only from various inorganic substances but also from foreign matter derived from non-polyester resins and that can be used to obtain various high-quality products similar to those produced from virgin polyester resins has not yet been obtained. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Special Publication No. 42-8855 [Patent Document 2] Japanese Patent Publication No. 48-62732 [Patent Document 3] Japanese Patent Application Publication No. 60-248646 [Patent Document 4] JP 2005-171138 A [Patent Document 5] Patent No. 6297351 Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention aims to solve the above problems and provide a recycled polyester resin that is a copolymer polyester resin made from recycled polyester raw materials derived from used polyester products or recycled polyester raw materials derived from scraps generated in the process of manufacturing polyester resins and products, and that can be used to manufacture polyester products in various forms. It also aims to provide a manufacturing method by which such a recycled polyester resin of the present invention can be obtained.
[0014] Means for Solving the Problems of the Prior Art The present inventors conducted extensive research in light of the problems of the prior art and discovered that a recycled polyester resin having a reduced amount of foreign matter and thermal stability similar to that of virgin polyester resin can be obtained by using recycled polyester raw materials and a specific manufacturing method, thereby completing the present invention. [Means for solving the problem]
[0015] That is, the present invention relates to the following (i) to (iv). (i) A recycled polyester resin containing a component derived from at least one type of recycled polyester raw material, i.e., a) used polyester products and b) unused polyesters generated in the process of manufacturing polyester products, the recycled polyester resin being characterized in that it satisfies all of the following (1) to (4): (1) All components of polyester acid When the total amount of the components is 100 mol %, 80 mol % or more is terephthalic acid, (2) When the total amount of all glycol components is taken as 100 mol %, ethylene glycol is 80 mol % or more, cyclohexanedimethanol is 2 mol % or more and 15 mol % or less, and diethylene glycol is 4 mol % or less, (3) The carboxyl end group concentration is 40 equivalents / t or less, (4) The average pressure rise rate is 0.6 MPa / h or less (however, the average pressure rise rate is a value calculated by the following procedure: a pressure rise tester including an extruder and a pressure sensor is used, a stainless steel filter (nominal mesh size: 1400 mesh, weave: twill weave, vertical mesh: 165 mesh, horizontal mesh: 1400 mesh, vertical wire diameter: 0.07 mm, horizontal wire diameter: 0.04 mm, filtration grain size: 12 μm) is set at the tip of the extruder, polyester resin is melted at 300°C in the extruder, and the polyester resin is extruded from the filter at a discharge rate of 29.0 g / min. The pressure value at the start of extrusion is defined as the "initial pressure value (MPa)" and the pressure value at the time of continuous extrusion for 12 hours thereafter is defined as the "final pressure value (MPa)." Based on these pressure values, the above average pressure rise rate is calculated by the following formula A: Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12) A) (ii) A molded product containing the recycled polyester resin described in (i). (c) Fibers containing the recycled polyester resin described in (a). (iv) A method for producing a recycled polyester resin using at least one type of recycled polyester raw material, which is a) a used polyester product and b) an unused polyester generated in a process for producing a polyester product, the method comprising all of the following steps (1) to (3): (1) a process for obtaining a reaction product containing a depolymerization product by adding a recycled polyester raw material to a mixture containing ethylene terephthalate oligomer, ethylene glycol, and cyclohexane dimethanol so that the molar ratio of total glycol components / total acid components is 1.10 to 1.30, and carrying out depolymerization under heat treatment conditions of 245 to 280°C; (2) passing the reaction product through a filter having a filtration grain size of 10 to 25 μm to recover the filtrate; (3) adding a polymerization catalyst to the filtrate and carrying out a polycondensation reaction of the depolymerization at a temperature of 260° C. or higher and a reduced pressure of 1.0 hPa or lower; Effect of the Invention
[0016] The recycled polyester resin of the present invention contains at least one recycled polyester raw material, i.e., a) used polyester products and b) unused polyesters generated in the process of manufacturing polyester products, but has a small amount of foreign matter mixed in, and the carboxyl end group concentration and diethylene glycol content satisfy specific ranges, and has excellent thermal stability. Therefore, for example, in the process of obtaining fibers by melt spinning, the process of obtaining sheets or films by film formation, and the process of obtaining molded products such as bottles, continuous operation over a relatively long period of time is possible, and products in various forms can be produced with good productivity. And, since it is a copolymerized polyester resin containing a copolymerization component while being a recycled polyester resin, it can be suitably used for molded products such as bottles that require transparency and fiber applications that require adhesiveness. Furthermore, according to the method for producing the recycled polyester resin of the present invention, it is possible to obtain the recycled polyester resin of the present invention with good operability and low cost without requiring complicated steps or equipment, and thus has great practical advantages. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below. The recycled polyester resin of the present invention (the resin of the present invention) is a polyester resin containing a component derived from at least one recycled polyester raw material, which is a) a used polyester product and b) an unused polyester generated in the process of manufacturing a polyester product. These components form a part of the polyester constituting the resin of the present invention.
[0018] Examples of used polyester products in the above category a) include polyester molded products (including fibers) that were once on the market and then collected after use, etc. Representative examples of such products include containers such as PET bottles and packaging materials. The unadopted polyester generated in the manufacturing process of polyester products mentioned in b) above is polyester that has not been commercialized. Examples of such unadopted polyester include off-standard resin pellets, materials that are no longer needed during molding, pieces cut during molding, scraps generated during molding or processing, cut-up pieces of transitional products generated when changing brands, and cut-up pieces of prototypes or defective products.
[0019] The above-mentioned a) and b) are not limited in their form, and may be pelletized by further processing such as crushing and cutting as necessary, or may be melted and pelletized. The above-mentioned a) and b) may be used alone or in combination.
[0020] The recycled polyester raw materials a) and b) above may be either crystalline or amorphous. Therefore, for example, pellets of amorphous polyester waste that have not been heat-treated, crystalline pellets that have been heat-treated, or a mixture of crystalline pellets and amorphous pellets can be used. In the present invention, it is preferable to use crystalline recycled polyester raw materials, particularly for the purpose of preventing fusion between pellets during charging into the can or depolymerization reaction. Therefore, the materials a) or b) above that have been crystallized by heat treatment (crystallized pellets, etc.) can be suitably used.
[0021] The properties of the recycled polyester raw materials in a) and b) above are not limited, and may be in the form of a) and b) above, or may be in the form of cut pieces, crushed materials (powder), etc. obtained by further processing such as cutting and crushing, as well as in the form of solids such as molded bodies (pellets, etc.) obtained by molding these. More specifically, pellets obtained by cooling and cutting melted polyester waste, and cut pieces obtained by finely cutting polyester molded products such as PET bottles are exemplified. In addition, the above-mentioned cut pieces, crushed materials (powders), etc. may be in the form of liquid obtained by dispersing or dissolving them in a solvent. When producing polyester products using these raw materials, they can be melted at a temperature above their melting point as necessary and charged into a can as a melt.
[0022] The recycled polyester resin of the present invention preferably contains 40% by mass or more, and more preferably 50% by mass or more, of the recycled polyester raw material which is at least one of the above a) and b). If the content of the recycled polyester raw material is less than 40% by mass, the objective of considering environmental issues cannot be achieved. Although there is no particular upper limit to the content of the recycled polyester raw material, according to the manufacturing method of the present invention described later, it is possible to easily obtain a recycled polyester resin with a recycled polyester raw material content of 40 to 80% by mass.
[0023] In the resin of the present invention, when the total amount of all acid components constituting the polyester is taken as 100 mol %, 80 mol % or more is terephthalic acid, that is, the acid component is mainly terephthalic acid. The proportion of terephthalic acid in the acid component is 80 mol % or more, and the proportion of terephthalic acid is preferably 90 mol %. If the proportion of terephthalic acid is less than 80 mol %, the crystallinity of the resin composition decreases and it tends to become amorphous, which is not preferable.
[0024] When the total amount of all glycol components is taken as 100 mol %, ethylene glycol is 80 mol % or more, cyclohexanedimethanol is 2 mol % to 15 mol % and diethylene glycol is 4 mol % or less. The copolymerization amount of cyclohexanedimethanol is preferably adjusted within the range of 2 to 15 mol% depending on the application of the resulting recycled polyester resin. For example, when used for molding applications, the copolymerization amount of cyclohexanedimethanol is preferably 4 to 15 mol%. Of these, 4 to 8 mol% is preferable. By copolymerizing 2 to 15 mol% of cyclohexanedimethanol, the crystallization speed of the polyester resin can be adjusted to one suitable for direct blow molding, and whitening due to crystallization during direct blow molding can be prevented. The melting point of the resulting recycled polyester resin is preferably 210 to 250°C.
[0025] If the copolymerization amount of cyclohexanedimethanol is less than 2 mol%, the crystallization speed of the resin composition is high, so that the molded product crystallizes and whitens during direct blow molding, resulting in poor transparency.On the other hand, if the copolymerization amount of cyclohexanedimethanol is more than 15 mol%, the resin composition becomes amorphous, so blocking is likely to occur during high-temperature drying or in the solid-phase polymerization process.
[0026] In the resin of the present invention, when the total amount of all glycol components is taken as 100 mol %, ethylene glycol is 80 mol % or more of the total glycol components, and preferably 85 mol % or more. If the content of ethylene glycol is less than 80 mol %, the crystallinity and heat resistance of the obtained polyester resin will be inferior.
[0027] In addition, when the total amount of all glycol components is 100 mol%, the diethylene glycol content of the resin of the present invention is 4 mol% or less, and preferably 3 mol% or less. In particular, in the resin of the present invention obtained by the production method of the present invention, ethylene glycol is used as one of the raw materials, and diethylene glycol may be generated as a by-product. The resin of the present invention has a small amount of diethylene glycol as a by-product, and has an excellent thermal stability due to the diethylene glycol content of 4 mol% or less. Therefore, it is possible to obtain molded products such as fibers, injection molded products, various blow molded products, sheets, and films with good productivity. The lower limit of the diethylene glycol content can be, for example, about 0.5 mol%, but is not limited thereto.
[0028] Examples of the acid component other than terephthalic acid in the resin of the present invention include isophthalic acid, phthalic acid, 5-sodium sulfoisophthalic acid, phthalic anhydride, naphthalenedicarboxylic acid, adipic acid, sebacic acid, dimer acid, and the like. Two or more of these may be used in combination, and ester-forming derivatives of these acids may also be used.
[0029] In addition, examples of diol components that can be used in the resin of the present invention other than ethylene glycol, cyclohexanedimethanol, and diethylene glycol in the total glycol components include neopentyl glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, dimer diol, an ethylene oxide adduct of bisphenol S, and an ethylene oxide adduct of bisphenol A.
[0030] The polycondensation catalyst is not limited, but may be at least one of germanium compounds, antimony compounds, titanium compounds, cobalt compounds, etc. Among them, at least one of germanium compounds and antimony compounds is particularly used. When the transparency of the resulting recycled polyester resin is important, it is preferable to use a germanium compound. Examples of the above compounds include oxides, inorganic acid salts, organic acid salts, halides, sulfides, etc. of germanium, antimony, titanium, cobalt, etc.
[0031] The amount of the polycondensation catalyst used is not particularly limited, but is preferably 5×10-5 mol / unit or more, more preferably 6×10-5 mol / unit or more, per mol of the acid component of the polyester resin to be produced. The upper limit of the amount used can be, for example, about 1×10-3 mol / unit, but is not limited thereto.
[0032] In addition, since the polymerization catalyst contained in the recycled polyester raw material may also act as a catalyst during the polycondensation reaction, it is preferable to take into consideration the type and content of the polymerization catalyst contained in the recycled polyester raw material when adding a polymerization catalyst in the polycondensation step.
[0033] During the polycondensation reaction, if necessary, a fatty acid ester capable of adjusting the melt viscosity, a hindered phenol-based antioxidant, or a phosphorus compound capable of suppressing thermal decomposition of the resin can be added together with the above-mentioned polycondensation catalyst.
[0034] Examples of fatty acid esters include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, pentaerythritol tetrastearate, dipentaerythritol hexastearate, etc. Among these, glycerin monostearate, pentaerythritol tetrastearate, and dipentaerythritol hexastearate are preferred. These can be used alone or in combination of two or more.
[0035] Examples of the hindered phenol antioxidants include 2,6-di-t-butyl-4-methylphenol, n-octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane, tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 4,4'-butylidenebis-(3-methyl-6-t-butylphenol), tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, ... Ethylene glycol-bis[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionate], 3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1'-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, etc. are used, but tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane is preferred in terms of effectiveness and cost. These can be used alone or in combination of two or more.
[0036] Examples of phosphorus compounds that can be used include phosphorous acid, phosphoric acid, trimethyl phosphite, triphenyl phosphite, tridecyl phosphite, trimethyl phosphate, tridecyl phosphate, triphenyl phosphate, etc. These compounds can be used alone or in combination of two or more.
[0037] The resin of the present invention has the above-mentioned composition and also has the following characteristic values. (a) Carboxyl end group concentration is 40 equivalents / t or less (b) The average pressure rise rate measured by a pressure rise tester is 0.6 MPa / h or less. The resin of the present invention having these characteristic values can be obtained by the production method of the present invention described below.
[0038] First, the resin of the present invention has the characteristic value (a) of a carboxyl end group concentration of 40 equivalents / t or less, preferably 30 equivalents / t or less, and more preferably 25 equivalents / t or less. The resin of the present invention has an excellent heat resistance due to the carboxyl end group concentration of 40 equivalents / t or less, and it is possible to produce molded products having excellent heat resistance with good productivity by various molding methods.
[0039] The intrinsic viscosity of the recycled polyester resin of the present invention is not particularly limited, but is usually preferably about 0.44 to 0.80. The recycled polyester resin of the present invention can also be used for molding applications by being highly polymerized through a solid-phase polymerization process, as described below. In this case, the intrinsic viscosity of the resulting recycled polyester resin is preferably 0.80 to 1.25. The intrinsic viscosity (IV) is measured at a temperature of 20°C using an equal mass mixture of phenol and tetrachloroethane as a solvent.
[0040] The resin of the present invention has a characteristic value (b) of an average pressure rise rate measured by the following method of 0.6 MPa / h or less, preferably 0.5 MPa / h or less, and more preferably 0.4 MPa / h or less. The average pressure rise rate in the present invention is an index of the amount of foreign matter derived from various inorganic substances or foreign matter derived from non-polyester resins, and a smaller average pressure rise rate indicates a smaller amount of foreign matter. The lower limit of the average pressure rise rate can be, for example, about 0.01 MPa / h, but is not limited thereto.
[0041] The average pressure rise rate was measured using a pressure rise tester including an extruder and a pressure sensor. A stainless steel filter (nominal mesh size: 1400 mesh, weaving method: twill weave, vertical mesh: 165 mesh, horizontal mesh: 1400 mesh, vertical wire diameter: 0.07 mm, horizontal wire diameter: 0.04 mm, filtration grain size: 12 μm) was set at the tip of the extruder, polyester resin was melted at 300° C. in the extruder, and the discharge rate from the filter was 29.0 g / min. Polyester Resin The pressure value applied to the filter when extruding is defined as the "initial pressure value (MPa)" at the start of extrusion, and the pressure value at the point when extrusion has been continued for 12 hours thereafter as the "final pressure value (MPa)." Based on these pressure values, the average pressure rise rate is calculated using the following formula A. Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12) A)
[0042] By employing the production method described below, the amount of foreign matter derived from various inorganic substances and foreign matter derived from non-polyester resins can be reduced in the resin of the present invention, and therefore it is possible to reduce the average pressure rise rate measured by a pressure rise tester, which is the characteristic value of (b), to 0.6 MPa / h or less.
[0043] Next, a method for producing the resin of the present invention will be described. In the production method of the present invention, it is important to carry out the steps (1) to (3) in this order. (1) a step of adding recycled polyester raw material to a mixture containing ethylene terephthalate oligomer, ethylene glycol, and cyclohexanedimethanol so that the molar ratio of total glycol components / total acid components is 1.10 to 1.30, and performing depolymerization under heat treatment conditions of 245 to 280° C. to obtain a reaction product containing a depolymerization product; (2) passing the reaction product through a filter having a filtration particle size of 10 to 25 μm to recover a filtrate; (3) A step of adding a polymerization catalyst to the filtrate and carrying out a polycondensation reaction at a temperature of 250° C. or higher and a reduced pressure of 1.0 hPa or less.
[0044] First, in the depolymerization step (1), a recycled polyester raw material is added to a mixture containing ethylene terephthalate oligomer, ethylene glycol, and cyclohexanedimethanol so that the molar ratio of total glycol components / total acid components is 1.10 to 1.30, and depolymerization is performed under heat treatment conditions of 245 to 280°C to obtain a reaction product containing a depolymerization product.
[0045] The ethylene terephthalate oligomer, ethylene glycol, and cyclohexanedimethanol may be any of known or commercially available products, or may be produced by known production methods.
[0046] In particular, as the ethylene terephthalate oligomer, for example, an esterification reaction product of ethylene glycol and terephthalic acid can be suitably used. The number average degree of polymerization of the ethylene terephthalate oligomer is not limited, but can be, for example, about 2 to 20.
[0047] The amount of the mixture containing ethylene terephthalate oligomer, ethylene glycol and cyclohexanedimethanol (hereinafter sometimes referred to as mixture E) is preferably 20 to 80 mass%, more preferably 30 to 70 mass%, of the final recycled polyester resin (100 mass%). If the amount of mixture E is less than the above amount, the recycled polyester raw material is likely to block with itself when the recycled polyester raw material is added, which is undesirable because it places an excessive load on the mixer. On the other hand, if the amount of mixture E is more than the above range, no particular problem occurs in the depolymerization reaction, but the recycling rate of the finally obtained recycled polyester resin is undesirably low.
[0048] In step (1), the proportions of ethylene terephthalate oligomer, ethylene glycol, cyclohexane dimethanol, and recycled polyester raw materials to be added may be appropriately changed depending on the copolymerization amount of isophthalic acid in the polyester resin to be finally obtained, but in general, it is preferable to add them in the following proportions (total of 100 parts by mass): 5 to 50 parts by mass of ethylene terephthalate oligomer, 1 to 18 parts by mass of ethylene glycol and cyclohexane dimethanol in total, and 40 to 80 parts by mass of recycled polyester raw materials are preferable.
[0049] In particular, the total amount of ethylene glycol and cyclohexanedimethanol to be added is preferably 1 to 15 parts by mass, more preferably 3 to 13 parts by mass, in order to sufficiently advance the depolymerization reaction. If the total amount exceeds 18 parts by mass, the ethylene terephthalate oligomer tends to solidify in the reactor, which may make it impossible to continue the subsequent reaction, and this is not preferred. In the mixture E, when ethylene glycol or cyclohexanedimethanol is added to the ethylene terephthalate oligomer, it is preferable to uniformize the temperature of the contents while rotating the stirrer in order to prevent the oligomer from solidifying.
[0050] In step (1), when the recycled polyester raw material is added to mixture E, depolymerization is carried out under heat treatment conditions of 245 to 280°C while stirring so that the molar ratio of total glycol components / total acid components becomes 1.10 to 1.30. In the production method of the present invention, this step is important. That is, in the conventional method using recycled polyester raw materials, depolymerization is carried out using only recycled polyester raw materials, but in the present invention, depolymerization of recycled polyester raw materials is carried out in the presence of ethylene terephthalate oligomer, ethylene glycol, and cyclohexane dimethanol, and the recycled polyester raw materials are added and depolymerized in such a manner that all components of the recycled polyester raw materials in the mixture E are such that the molar ratio of total glycol components / total acid components is 1.10 to 1.30.
[0051] By carrying out the above-mentioned step (1), not only various inorganic substances but also foreign substances derived from non-polyester resins are efficiently precipitated, so that these foreign substances can be filtered out without fail in the step (2).Then, in the polycondensation reaction in the step (3), it becomes possible to obtain a recycled polyester resin having a diethylene glycol content (copolymerization amount) and a carboxyl end group concentration that are not more than a specific amount as characteristic values of the present invention, and having a small amount of foreign substances mixed in. Furthermore, by carrying out depolymerization of recycled polyester raw materials in the presence of ethylene terephthalate oligomer, ethylene glycol and cyclohexanedimethanol, the presence of copolymerization components makes it possible to proceed with the depolymerization reaction at a lower temperature than when depolymerization is carried out using only recycled polyester raw materials, which is a great advantage when carried out on an industrial scale.
[0052] In the production method of the present invention, it is preferable that the recycled polyester raw material is not decomposed into monomers by the depolymerization reaction, but is decomposed into oligomers having a repeating unit of about 5 to 20. By controlling the depolymerization reaction in this way, not only various inorganic substances but also foreign substances derived from non-polyester resins are efficiently precipitated, so that a larger amount of foreign substances can be removed.
[0053] If the molar ratio of total glycol components / total acid components during the depolymerization reaction is outside the above range, the resulting recycled polyester resin will not satisfy at least one of the carboxyl end group concentration and diethylene glycol content specified in the present invention, and will have a high average pressure rise rate. This is because, when the molar ratio of total glycol components / total acid components during the depolymerization reaction is outside the above range, the precipitation of various inorganic substances and foreign substances derived from non-polyester resins is not efficiently carried out, and these foreign substances cannot be filtered out completely in step (2), and the foreign substances precipitate after the polycondensation reaction in step (3), resulting in a recycled polyester resin with a high average pressure rise rate.
[0054] The reactor used in the production method of the present invention may be a commonly used esterification reactor without any particular problem in terms of volume and shape of the stirring blades. However, in order to efficiently advance the depolymerization reaction, it is preferable that the reactor has a structure equipped with a distillation column that does not distill ethylene glycol outside the system. When the recycled polyester raw material is charged, it is preferable to do so while stirring under normal pressure, and it is more preferable to charge it in a state where it is purged with a small amount of inert gas (generally nitrogen gas is used).
[0055] The reaction temperature during depolymerization in step (1) is preferably set at an internal temperature of the reactor in the range of 245 to 280°C, and more preferably set at an internal temperature in the range of 255 to 280°C. If the reaction temperature during depolymerization is less than 245°C, the reaction product solidifies, the operability deteriorates, and even if a recycled polyester resin is obtained, the diethylene glycol content and the carboxyl end group concentration become too high. If the reaction temperature exceeds 280°C, the diethylene glycol content and the carboxyl end group concentration of the obtained recycled polyester resin become too high. In addition, the depolymerization reaction time (the reaction time from the end of the addition of the recycled polyester raw material) is preferably within 4 hours, and more preferably within 2 hours from the viewpoints of suppressing the amount of diethylene glycol as a by-product and suppressing deterioration of the color tone of the polyester.
[0056] In step (2), the reaction product containing the depolymerized polymer from step (1) is passed through a filter with a filtration particle size of 10 to 25 μm to filter out foreign matter. As described above, by carrying out the depolymerization reaction under the conditions of step (1), not only various inorganic substances but also foreign matter derived from non-polyester resins is efficiently precipitated, and by passing the reaction product through a filter with a filtration particle size of 10 to 25 μm, the precipitated foreign matter can be filtered out, and a filtrate containing a small amount of foreign matter can be obtained. If a filter with a filtration particle size of more than 25 μm is used, foreign matter in the polymer cannot be sufficiently removed, and the resulting recycled polyester resin contains a large amount of foreign matter. Therefore, when such a resin is used for spinning, the nozzle pack pressure increases and thread breakage occurs. On the other hand, if a filter with a filtration particle size of less than 10 μm is used, clogging due to foreign matter easily occurs, and the filter life is shortened, which is disadvantageous in terms of cost and also deteriorates operability.
[0057] As the filter that can be used in the step (2) of the present invention, any ordinary filter can be used without any particular problem, and examples thereof include a screen changer type filter, a leaf disk filter, and a candle type sintered filter.
[0058] In the production method of the present invention, the above-mentioned polymerization catalyst is added to the filtrate obtained through the above step (2), and a polycondensation reaction is carried out at a temperature of 260° C. or higher and under a reduced pressure of 1.0 hPa or lower.
[0059] Then, in the polycondensation reaction tank, the polycondensation reaction is carried out at a temperature of 260° C. or higher and under reduced pressure of 1.0 hPa or lower. If the polycondensation reaction temperature is lower than 260° C. or the pressure during the polycondensation reaction exceeds 1.0 hPa, the polycondensation reaction time becomes long, resulting in poor productivity. The polycondensation reaction temperature is more preferably 270° C. or higher. However, if the polycondensation reaction temperature is too high, the polymer will be colored due to thermal decomposition, the color tone will deteriorate, and the amount of terminal groups (COOH) will also increase due to thermal decomposition, so in the present invention, the upper limit of the polycondensation reaction temperature is preferably 285° C. or lower. The intrinsic viscosity of the recycled polyester (prepolymer) obtained here is preferably 0.44 to 0.80.
[0060] The resin of the present invention may contain various additives other than the above-mentioned polymerization catalyst, antioxidant, phosphorus compound, etc., so long as the effect of the resin is not impaired. As various additives, additives such as manganese compounds such as manganese acetate, anthraquinone dye compounds, copper phthalocyanine compounds, etc. may be contained in order to suppress coloration due to thermal decomposition of the polyester resin.
[0061] Next, the prepolymer obtained by the melt polymerization reaction is made into chips of any shape such as a die shape or a cylinder shape, and the polyester chips are continuously fed to a crystallizer and crystallized at a temperature of 150 to 190 ° C., then fed to a dryer and dried at a temperature of 190 ° C. or less for 4 to 16 hours, then fed to a preheater and heated to the solid-phase polymerization temperature described below for 2 to 5 hours, and then continuously fed to a solid-phase polymerization machine for solid-phase polymerization reaction to obtain a polyester resin with a target intrinsic viscosity. The solid-phase polymerization is preferably carried out under an inert gas such as nitrogen gas. The solid-phase polymerization is usually preferably carried out at a temperature within the range of 170 to 230 ° C., more preferably at a temperature within the range of 180 to 220 ° C. The polymerization time is 20 to 80 hours, and the reaction is carried out in the solid-phase polymerization machine.
[0062] The resin of the present invention can be used to obtain molded articles (blow molded articles, injection molded articles, sheets, films, etc.) with excellent color tone and transparency by employing blow molding, injection molding, stretching methods, etc., and can also be used to obtain fibers by melt spinning.
[0063] Molded articles containing the resin of the present invention can be produced by applying various molding methods such as press molding, extrusion molding, compressed air molding, and blow molding using raw materials containing the resin of the present invention. This makes it possible to provide various parts, including containers. The resin of the present invention is particularly suitable for producing blow molded articles because it has properties similar to those of virgin polyester resin and has excellent thermal stability. Therefore, a manufacturing method for a molded article can be suitably adopted, which includes a step of obtaining a parison from a melt of raw materials containing the resin of the present invention and a step of blowing gas into the parison. This makes it possible to produce molded articles such as containers.
[0064] As described above, the resin of the present invention has excellent thermal stability due to the diethylene glycol content and carboxyl end group concentration being below a specific amount. Therefore, when obtaining the above-mentioned molded article, thickness unevenness is unlikely to occur, and molded articles with high uniformity can be obtained with good operability. Furthermore, as described above, the resin of the present invention has an average pressure increase rate of 0.6 MPa / h or less, and has a small amount of foreign matter mixed in. Foreign matter present in the resin is assumed to be inorganic matter or foreign matter derived from non-polyester resins, but the small amount of these foreign matters makes it possible to obtain molded articles with good surface appearance and excellent impact resistance and strength.
[0065] In the case of molded products, the inclusion of 0.1 to 1.0 mass % of a hindered phenol-based antioxidant can prevent a decrease in intrinsic viscosity and deterioration of color tone after molding.
[0066] In the case of a molded product, it is preferable to use a germanium compound and a cobalt compound as a polymerization catalyst. The germanium compound is added at a concentration of 5.0×10 per 1 mol of the acid component of the polyester. -5 Molar ~ 3.0 x 10 -4 It is preferable that the content is 1.0×10 -5 If the amount is less than 3.0×10 mol, it becomes difficult to obtain a polyester resin with a desired polymerization degree. -4If the amount exceeds 1 mole, the by-products produced by the reaction between the cobalt compound and the germanium compound deteriorate the stability of the polyester over time, causing a decrease in the intrinsic viscosity of the polyester resin composition after long-term storage and a deterioration in color tone, which is undesirable.
[0067] Examples of the germanium compound include germanium dioxide, germanium tetrachloride, and germanium tetraethoxide. From the viewpoints of polymerization catalyst activity, physical properties of the resulting polyester resin, and cost, germanium dioxide is preferred.
[0068] The content of the cobalt compound is 1.0×10 per mole of the acid component of the polyester. -5 Molar ~ 1.0 x 10 -4 It is necessary to have a mole ratio of 2.0 x 10 -5 Molar ~ 8.0 x 10 -5 It is preferably molar. If it is less than 1.0×10-5 moles, the color tone of the polyester deteriorates. On the other hand, if it is less than 1.0×10 -4 If the amount exceeds 1 mole, the stability over time of the polyester resin deteriorates. Examples of the cobalt compound include cobalt acetate, cobalt formate, cobalt chloride, cobalt oxide, etc., and from the viewpoints of polymerization catalyst activity, physical properties of the resulting polyester resin, and cost, cobalt acetate is preferred. In the case of fibers containing the resin of the present invention, the fibers can be produced by a production method including a step of melting and spinning a raw material containing the resin of the present invention. This makes it possible to produce ultrafine fibers having a single fiber fineness of 0.8 decitex or less (preferably 0.6 to 0.3 decitex). The spinning method can be carried out according to known conditions.
[0069] As described above, the resin of the present invention has a relatively low content of foreign matter and has properties equivalent to those of virgin polyester resin, and therefore, troubles such as yarn breakage are unlikely to occur in any of the melt spinning, drawing / heat treatment and winding steps, and polyester fibers can be obtained with good productivity.
[0070] The fiber of the present invention containing the resin of the present invention may be, for example, either a monofilament or a multifilament, and may be either a long fiber or a short fiber. EXAMPLES
[0071] The present invention will now be described in detail with reference to examples, in which the measurement and evaluation methods for various property values and the like are as follows. (a) Intrinsic viscosity The resulting recycled polyester resin is used, and measurements are made at 20°C using an equal mass mixture of phenol and tetrachloroethane as the solvent. (b) Composition of polyester resin The obtained recycled polyester resin was dissolved in a mixed solvent of deuterated trifluoroacetic acid and deuterated chloroform in a volume ratio of 1 / 11, and 1H-NMR was measured using a JEOL JNM-ECZ400R / S1 NMR device. The type and content of the copolymerization components were determined from the integrated intensity of the proton peaks of each component in the obtained chart. (c) Carboxyl end group concentration 0.1 g of the resulting recycled polyester resin was dissolved in 10 ml of benzyl alcohol, and 10 ml of chloroform was added to the solution, which was then titrated with a 1 / 10 N solution of potassium hydroxide in benzyl alcohol to determine the content. (d) Average boost rate measured by a boost test machine The obtained recycled polyester resin was melted at 300°C in an extruder, and a stainless steel twill weave filter (nominal mesh size: 1400 mesh, weaving method: twill weave, vertical mesh: 165 mesh, horizontal mesh: 1400 mesh, vertical wire diameter: 0.07 mm, horizontal wire diameter: 0.04 mm, filtration grain size: 12 μm, viscous resistance coefficient (m-1): 2.60 × 107, inertial resistance coefficient: 5.14 × 10, manufactured by Kamijo Seiki Co., Ltd.) was set as a filter at the tip of the extruder, and a reinforcing material (stainless steel plain weave wire mesh (nominal mesh size: 165 mesh, horizontal mesh: 1400 mesh, vertical wire diameter: 0.07 mm, horizontal wire diameter: 0.04 mm, filtration grain size: 12 μm, viscous resistance coefficient (m-1): 2.60 × 107, inertial resistance coefficient: 5.14 × 10, manufactured by Kamijo Seiki Co., Ltd.) was further set on the back side (downstream side) of the filter. After laminating a filter (fiberglass: 40 mesh, weave: plain weave, wire diameter: 0.21 mm, manufactured by Kamijo Seiki Co., Ltd.), the polymer discharge rate was set to 29.0 g / min, and the filter pressure was measured using a pressure rise tester; Asahi Gauge Co., Ltd. "MES-Y44D type" detector. The pressure rise test using the pressure rise tester was performed continuously for 12 hours, and the average pressure rise rate was calculated from the initial pressure value (MPa) at the start of the pressure rise test (the minimum pressure value between 5 and 10 minutes after the polyester resin began to pass through the filter is taken as the initial pressure) and the final pressure value (MPa) after 12 hours had elapsed, using the following formula. Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12
[0072] (e) Melting point, (f) Glass transition temperature The obtained recycled polyester resin was measured using a PerkinElmer differential scanning calorimeter (Diamond DSC) in a nitrogen stream at a temperature range of 25° C. to 280° C., a temperature increase (decrease) rate of 20° C. / min, and a sample weight of 8 mg. (g) Formability The thickness of the body of the resulting containers (100 samples) was measured, and those with a difference in thickness between the thickest and thinnest parts of up to 0.30 mm were deemed to have passed. Depending on the number of samples that passed, they were evaluated in two stages as follows: 〇: 95 or more passing samples ×: 94 or fewer samples passed
[0073] (h) Haze Sample pieces (20 pieces) were cut out from the obtained container, and the turbidity was measured using a turbidity meter Model 1001DP manufactured by Nippon Denshoku Industries Co., Ltd. (air: haze 0%), and the average value was calculated for n=20. The smaller this value, the better the transparency, and a value of 6% or less was judged to be excellent transparency. (i) Impact resistance (g) Molded products that passed the moldability evaluation (100 samples) were filled with 340 ml of tap water and dropped once on a P tile from a height of 200 cm at room temperature with the bottom side facing down and once with the side facing down. Impact resistance was evaluated based on the number of molded products that did not break. If 90 or more samples were dropped, the impact resistance was evaluated as good.
[0074] Example 1 [Recycled polyester resin] A slurry of terephthalic acid (TPA) and ethylene glycol (EG) (TPA / EG molar ratio = 1 / 1.6) was supplied to an esterification reactor and reacted at a temperature of 250°C and a pressure of 50 hPa to obtain ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95%. 40.0 parts by mass of ethylene terephthalate oligomer was charged into an esterification reactor, followed by 2.7 parts by mass of cyclohexanedimethanol (CHDM) and 3.3 parts by mass of ethylene glycol (EG) to obtain a mixture E. Then, 54 parts by mass of recycled polyester raw material (pellet-like polyester waste generated in the process of manufacturing polyester resin) was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material was added so that the molar ratio of total glycol components / total acid components (hereinafter sometimes referred to as G / A) was 1.15. After that, the depolymerization reaction was carried out under heat treatment conditions of 260°C for 1 hour. The obtained depolymerization product was then pumped into a polycondensation reactor (hereinafter referred to as a PC can) through a candle filter with a mesh size of 20 μm that was set between the esterification reactor and the polycondensation reactor. Germanium dioxide was then added at 1.0×10 -4mol / unit, cobalt acetate as a cobalt compound, and tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane (ADECA: Adekastab AO-60) as a hindered phenol-based antioxidant were added in amounts of 0.2 mass% relative to the polyester resin obtained, and the PC can was reduced in pressure, and after 60 minutes, a melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours, resulting in a polyester resin with an intrinsic viscosity of 0.7. The polyester resin thus obtained was then continuously fed to a crystallizer and crystallized at 150°C, fed to a dryer and dried at 130°C for 10 hours, sent to a preheater and heated to 180°C, and then fed to a solid-state polymerizer. A solid-state polymerization reaction was then carried out under nitrogen gas at 190°C for 50 hours to obtain a polyester resin with an intrinsic viscosity of 1.1.
[0075] [Blow Molded Products] The obtained recycled polyester resin was chipped and dried, and then extruded at 260°C using a direct blow molding machine (manufactured by Tahara) to form a cylindrical parison, which was then sandwiched between metal molds while still in a softened state to form a bottom, and then blown into a bottle. At this time, the bottom was formed when the parison had a diameter of 3 cm and a length of 25 cm, and a 350 ml hollow container (direct blow molded product) was obtained by blow molding.
[0076] Examples 2 to 8, Comparative Examples 1 to 9 [Recycled polyester resin] The depolymerization reaction was carried out in the same manner as in Example 1, except that the amounts of ethylene terephthalate oligomer, ethylene glycol, cyclohexanedimethanol, and recycled polyester raw material added during the depolymerization reaction, G / A, and heat treatment temperature were changed to those shown in Table 1. Further, polyester resins were produced in the same manner as in Example 1, except that the filtration particle size of the filter in the step of recovering the filtrate and the heat treatment temperature in the polymerization reaction step were changed to those shown in Table 1. Subsequently, the obtained polyester resin was subjected to a solid-phase polymerization reaction in the same manner as in Example 1 to obtain a polyester resin having an intrinsic viscosity of 1.1. [Blow Molded Products] The obtained polyester resin was used to carry out blow molding in the same manner as in Example 1 to obtain a blow molded article.
[0077] Table 1 shows the property values of the polyester resins obtained in Examples 2 to 8 and Comparative Examples 1 to 9, and the evaluation results of the moldability, haze, and impact resistance of the blow molded products.
[0078] [Table 1]
[0079] As is clear from Table 1, the recycled polyester resins obtained in Examples 1 to 8 had excellent moldability during blow molding because the amount of carboxyl terminal groups, the diethylene glycol content, and the average pressure rise rate were within the ranges specified in the present invention. The hollow containers obtained in Examples 1 to 8 had low haze and excellent transparency, and also had excellent impact resistance.
[0080] On the other hand, in Comparative Example 1, the diethylene glycol content was high and the thermal stability was poor because the G / A ratio during the depolymerization reaction was high, and the CHDM copolymerization amount was low at 1 mol%, so the crystallinity was high, and the obtained hollow container had poor haze, moldability, and impact resistance. In addition, the high G / A ratio resulted in insufficient removal of foreign matter, and the pressure rise rate was fast. In Comparative Example 2, the depolymerization in step (1) was performed under heat treatment conditions at 285°C, so the resulting recycled polyester resin had a high carboxyl end group concentration and a high diethylene glycol content. In addition, because both the carboxyl end group concentration and the diethylene glycol content were high, thermal decomposition of the recycled polyester resin occurred during molding, resulting in poor moldability and poor impact resistance of the resulting hollow container. In Comparative Example 3, the filtration particle size of the candle filter installed between the ES can and the PC can was 5 μm, so clogging occurred during filtration, and the process could not proceed to the polycondensation reaction, and a resin could not be obtained.
[0081] In Comparative Example 4, the filtration particle size of the candle filter installed between the ES can and the PC can was 30 μm, so the obtained recycled polyester resin had a large amount of foreign matter mixed in and a high average pressure rise rate. Therefore, the obtained hollow container had high haze, poor transparency, and poor impact resistance. In Comparative Example 5, the G / A during the depolymerization reaction was low, so the obtained recycled polyester resin had a high carboxyl end group concentration and a high average pressure rise rate. In addition, because the carboxyl end group concentration was high, thermal decomposition of the recycled polyester resin occurred during molding, causing deterioration in moldability, and the obtained hollow container had poor haze and impact resistance. In Comparative Example 6, the G / A of the depolymerization was high at 1.35, so the obtained recycled polyester resin had a high carboxyl end group concentration and a high diethylene glycol content, causing poor thermal stability, and also had a high average pressure rise rate. Therefore, moldability was deteriorated, and the obtained hollow container had poor haze and impact resistance. In Comparative Example 7, the depolymerization temperature was low, so the depolymerization of the recycled polyester did not proceed sufficiently, and a recycled polyester resin could not be obtained. In Comparative Example 8, the polycondensation reaction temperature was low, so the polycondensation reaction did not proceed sufficiently, and a recycled polyester resin could not be obtained.
Claims
1. A recycled polyester resin comprising a component derived from at least one recycled polyester raw material, i.e., a) used polyester product and b) unused polyester generated in the process of manufacturing the polyester product, and characterized in that the recycled polyester resin satisfies all of the following (1) to (4): (1) When the total amount of all acid components constituting the polyester is taken as 100 mol %, 80 mol % or more is terephthalic acid, (2) When the total amount of all glycol components is taken as 100 mol%, ethylene glycol is 80 mol% or more, cyclohexanedimethanol is 2 mol% or more and 15 mol% or less, and diethylene glycol is 4 mol% or less, (3) The carboxyl end group concentration is 40 equivalents / t or less, (4) The average pressure rise rate is 0.6 MPa / h or less (wherein the average pressure rise rate is a value calculated by the following procedure: a pressure rise tester including an extruder and a pressure sensor is used, a stainless steel filter (nominal mesh size: 1400 mesh, weave: twill weave, vertical mesh: 165 mesh, horizontal mesh: 1400 mesh, vertical line diameter: 0.07 mm, horizontal line diameter: 0.04 mm, filtration particle size: 12 μm) is set at the tip of the extruder, a polyester resin is melted at 300° C. in the extruder, and the polyester resin is extruded from the filter at a discharge rate of 29.0 g / min. The pressure value at the start of extrusion is defined as the "initial pressure value (MPa)", and the pressure value at the time of continuous extrusion for 12 hours thereafter is defined as the "final pressure value (MPa)". Based on these pressure values, the average pressure rise rate is calculated by the following calculation formula A: Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12) ... A)
2. A molded article comprising the recycled polyester resin according to claim 1.
3. A fiber comprising the recycled polyester resin according to claim 1.
4. A method for producing a recycled polyester resin using at least one recycled polyester raw material, which is a) a used polyester product and b) an unused polyester generated in a process for producing a polyester product, the method comprising all of the following steps (1) to (3): (1) A process for obtaining a reaction product containing a depolymerization product by adding a recycled polyester raw material to a mixture containing ethylene terephthalate oligomer, ethylene glycol, and cyclohexanedimethanol so that the molar ratio of total glycol components / total acid components is 1.10 to 1.30, and carrying out depolymerization under heat treatment conditions of 245 to 280° C.; (2) A step of passing the reaction product through a filter having a filtration particle size of 10 to 25 μm and recovering the filtrate. (3) A step of adding a polymerization catalyst to the filtrate and carrying out a polycondensation reaction of the depolymerization at a temperature of 260° C. or higher and a reduced pressure of 1.0 hPa or lower.
Citation Information
Patent Citations
JP1967008855Y1
JP1973062732A
Depolymerization of waste polyester
JP1985248646A
Semiconductor integrated circuit device
JP1987097351A
Production of polyester using scrap
JP1998310637A